DEVELOPMENT OF ELECTRONIC APPLICATIONS BASED ON MICROSOFT ACCESS IN KOPERASI INTI BANDUNG - Dessi Hartini; Maya Setiawardani; Mamun Sutisna (Ebiz Prima Nusa, 2022)
The Electronic Archiving Application applied in the Human Resources section of the INTI Cooperative is a crucial part in managing records because it is responsible for storing transaction records, legalities and employee data. Archives are the most basic and most important thing in administrative activities because archives have data information stored in them that is done. Archives Management In the Human Resources Cooperative INTI Bandung still uses the manual method. Manual archives are said to be ineffective because there is a risk of damage or loss of archives that still have use value. Based on the archive management phenomenon that occurred at the INTI Cooperative, the solution that was deemed appropriate was to design and create an electronic archival information system that aims to assist INTI Cooperatives in managing archives. Making Electronic Archive Applications is assisted by using the Microsoft Access system because it is simple and easy to use.